Electrochemical Mechanism of Tellurium Reduction in Alkaline Medium - Wu, Tingjun; Kim, Jiwon; Myung, Nosang V. (Frontiers in Chemistry, 2020)
A systematic electrochemical study was conducted to investigate the reduction of tellurium (Te) in alkaline solutions. The effect of various parameters including tellurite ion concentration, applied potential, and pH were investigated by both linear sweep voltammograms (LSVs) and electrochemical quartz crystal microbalance (EQCM). EQCM was essential to understand the reduction of Te (0) . At relatively weaker alkaline solutions (i.e., pH ≤ 12.5), the discharge of Te(OH)3 + was determined to be the ratelimiting step during the reduction of Te(IV) to Te(0). For the reduction of Te(0) to Te(-I), the reaction follows a 4-step reaction which consisted of two discharge and two electrochemical reactions. The second discharge reaction was the rate-limiting step when pH ≤ 12.5 with the Tafel slope of 120 mV/decade. At higher pH of 14.7, the Tafel slope was shifted to be 40 mV/decade which indicated the rate-limiting step was altered to the second electrochemical reaction. Te(0) deposits were found either on the surface of an electrode or in the solution depending on pH due to the different rate-limiting reactions, revealing that pH was a key parameter to dictate the morphology of the Te(0) deposits in alkaline media.